Role of Hydrology in Water Resources Management: Challenges and Cooperation in Hydrology for Water Resources Management (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The importance of hydrology is increasing because of the global growth of water needs and the rise of water scarcity, which together cause greater risk and unreliability in water resources management. The basic task of hydrology, which is fundamental for water resources management, is the accurate definition and control of the water balance for different space and time increments.The water balance equation is simple, but until now there are many unsolved problems surrounding it, such as the definition of catchment boundaries and areas, the accuracy of point precipitation measurement and the assessment of areal precipitation, the accuracy of actual areal évapotranspiration etc. Modern computer and numerically oriented hydrology tries to use most new scientific approaches, methods and technologies. Due to the influence of university education and papers published in leading international scientific journals, young scientists, in particular, believe that this is the sole way to advance knowledge.Experienced and practically oriented hydrologists do not always share their enthusiasm. Hydrology has to be loyal to its basic principles and roots, in order to be able to answer the complex challenges of water resources management which will come in the future. As water management is an interdisciplinary task, hydrology should be more connected with the other scientific disciplines and professions involved. Hydrology urgently needs close co-operation with many other human activities, especially those concerned with environmental issues.